EPEN-05. CXorf67 EXPRESSION IS A PUTATIVE DRIVER OF PFA EPENDYMOMA. Issue 2 (22nd June 2018) - Hübner, Jens-Martin; Okonechnikov, Konstantin; Wen, Ji; Orisme, Wilda; Tang, Bo; Jia, Sujuan; Tatevossian, Ruth; Zhang, Jinghui; Pfister, Stefan M; Pajtler, Kristian W; Ellison, David W; Kool, Marcel
Abstract: Ependymal tumors are brain neoplasms arising throughout all compartments of the central nervous system, with 10-year overall survival rates as low as 60% for pediatric patients. Molecular classification has identified nine molecular groups of ependymal tumors. Among those, the PFA group is associated with an especially dismal outcome and a clear driver for these tumors is yet to be identified. Strikingly, PFA tumors lack the repressive histone H3 lysine 27 trimethylation (H3K27me3) mark but, in contrast to pediatric high-grade gliomas, only a small fraction (~4%) of tumors harbor H3K27M mutations suggesting a different mechanism responsible for histone hypomethylation. Our studies have recently identified aberrant expression and mutations of CXorf67 as a hallmark of PFA ependymoma. Intriguingly, Co-Immunoprecipitation (Co-IP) experiments using a PFA cell line have shown an interaction of CXorf67 with EZH2 and SUZ12. Both of these proteins are core components of the polycomb repressive complex 2 (PRC2) that catalyzes trimethylation of H3K27. Further, knockdown experiments have shown that expression of CXorf67 inversely correlates with H3K27me3 levels strongly indicating a crucial role of CXorf67 in mediating PRC2 activity. Based on our results, we are proposing a model in which expression of CXorf67 leads to histone hypomethylation followed by a derepression of oncogenes which ultimately leads to tumor formation. To test this hypothesis, we performed ChIP-seq analyses for histone marks, EZH2, and CXorf67 in PFA ependymoma and other molecular groups and functional experiments in PFA cell lines to see how CXorf67 may regulate histone hypomethylation and tumorigenesis of PFA ependymoma.